Studying the Differences of Bacterial Metabolome and Microbiome in the Colon between Landrace and Meihua Piglets - Yan, Shijuan; Zhu, Cui; Yu, Ting; Huang, Wenjie; Huang, Jianfeng; Kong, Qian; Shi, Jingfang; Chen, Zhongjian; Liu, Qinjian; Wang, Shaolei; Jiang, Zongyong; Chen, Zhuang (Frontiers in Microbiology, 2017)
This study was conducted to compare the microbiome and metabolome differences inbacteria and bacterial metabolites in the colon lumen from two pig breeds with different genetic backgrounds, via microbiome and metabolome techniques. Fourteen weaned piglets at 30 days of age, including 7 Landrace piglets (a lean-type pig breed with a fast growth rate) and 7 Meihua piglets (a fatty-type Chinese local pig breed with a slow growth rate), were fed the same diets for 35 days. Untargeted metabolomics analyses showed that a total of 401 metabolites differed between Landrace and Meihua. Seventy of these 401 metabolites were conclusively identified. Landrace accumulated more short-chain fatty acids (SCFAs) and secondary bile acids in the colon lumen. Moreover, expression of the SCFAs transporter (solute carrier family 5 member 8, SLC5A8) and receptor (G protein-coupled receptor 41, GPR41) in the colon mucosa was higher, while the bile acids receptor (farnesoid X receptor, FXR) had lower expression in Landrace compared to Meihua. The relative abundances of 8 genera and 16 species of bacteria differed significantly between Landrace and Meihua, and were closely related to the colonic concentrations of bile acids or SCFAs based on Pearson’s correlation analysis. Collectively, our results demonstrate for the first time that there were distinct differences in the colonic microbiome and metabolome between Meihua and Landrace piglets, with the most profound disparity in production of SCFAs and secondary bile acids.